Discursos e representações sobre a natureza: o novo Código Florestal Brasileiro - Scarton, Laura Patrícia (2014)
This study aims to analyze the discourse related to the changes of the Brazilian Forest Code and the representations of Nature within this debate, using notions of Discourse Analysis Theory. The analysis rests on the dispute of opposite views established around the approval of the Law: environmentalists and ruralists. During this moment, the agents used several means to gather followers toward their vision and to influence voting. Brochures were one of the means used for this purpose. The corpus of this analysis is therefore constituted of two brochures elaborated by these two groups: the first belonging to a set of Non-Governmental Organizations (NGOs) called SOS Forests and the second to the Brazilian National Confederation of Agriculture (CNA Brazil). The general goal of this thesis is to analyze the discourses used in these two texts. Specific goals include trying to define the idea of nature existing behind each discourse, as well as evidencing the positions-subjects established in the discussion and the meaning of the man/Nature relation to/for the subjects. Firstly, a historical review is made of the idea of Nature by western culture, from magical Nature, passing through Greece, the Middle Ages and Enlightenment until current times. A synthetic dissertation on the country s existing Forest Codes follows. After the definition of some important concepts for Discourse Analysis, the proper reading of the material begins. Each brochure presented its position in regards to the Law project that gave origin to the newest Brazilian Forest Code, consequently exposing its arguments. A game of intentions can be observed in the analyzed brochures, given that both use arguments they believe in order to convince the reader of their point of view, but this position is previous to any intention. It speaks before, determined by experience, exteriority, derived from symbolic work. The documents consider only the farmer s position-subject and the environmentalist s position-subject, not considering that these categories include a set of practices that have different meanings and refer to different relations with nature. The positions-subjects refer differently to the meaning of Nature: according to the CNA brochure, it is neither untouched nor untouchable. On the contrary, nature is conceived here in its relation with man: the environment exists and is considered in its contact and manipulation by man. In the SOS Forests brochure, however, the interface with man is always of destruction, the environment as something external to mankind which lacks protection, since the intervention of people causes damage. One can conclude that, although belonging to different discursive formations, both are aligned to an anthropocentric view of Nature, given that neither breaks with the notion that things are made for mankind. The idea of Nature is different in each one, but a deeper analysis demonstrated that both come from a close place of memory.